2016
DOI: 10.3389/fnbeh.2016.00158
|View full text |Cite
|
Sign up to set email alerts
|

GLAST Deficiency in Mice Exacerbates Gap Detection Deficits in a Model of Salicylate-Induced Tinnitus

Abstract: Gap detection or gap pre-pulse inhibition of the acoustic startle (GPIAS) has been successfully used in rat and guinea pig models of tinnitus, yet this system has been proven to have low efficacy in CBA mice, with low basal GPIAS and subtle tinnitus-like effects. Here, we tested five mouse strains (CBA, BalbC, CD-1, C57BL/6 and 129sv) for pre-pulse inhibition (PPI) and gap detection with varying interstimulus intervals (ISI) and found that mice from a CBA genetic background had the poorest capacities of suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 70 publications
3
30
1
Order By: Relevance
“…GLAST KO mice 31 and their WT littermates were obtained from heterozygous (HET) crosses or from KO males crossed with HET females. Similar to what we previously reported, 24 we observed a non-mendelian distribution in the progeny of crosses between heterozygous KO mice (n = 200): 29% wild-type animals, 54% heterozygous knockout animals, and 15% homozygous knockout animals. Two percent of the pups had an unclear genotype.…”
Section: Experimental Animalssupporting
confidence: 90%
See 2 more Smart Citations
“…GLAST KO mice 31 and their WT littermates were obtained from heterozygous (HET) crosses or from KO males crossed with HET females. Similar to what we previously reported, 24 we observed a non-mendelian distribution in the progeny of crosses between heterozygous KO mice (n = 200): 29% wild-type animals, 54% heterozygous knockout animals, and 15% homozygous knockout animals. Two percent of the pups had an unclear genotype.…”
Section: Experimental Animalssupporting
confidence: 90%
“…Cochlear frequency mapping was then performed using a custom plug-in to ImageJ from NIH (Measure_Line.class from the Liberman laboratory at the Eaton-Peabody Laboratory). This gave the total length of the cochlea and their respective frequency points and was used as a guide obtaining confocal images for discrete frequency regions (6,8,12,16,24,32,48, and 64 kHz) along the length of the cochlea. Confocal z-stacks , with dimensions 1024 × 1024 and 16-bit image, along discrete regions of the basilar membrane were made with a 63× oil immersion objective (NA1.40) on a Zeiss LSM 880 confocal microscope.…”
Section: Immunohistochemistry and Quantification Of Synaptic Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, neonatal exposure to monosodium glutamate has been shown to induce neuronal atrophy and dysmorphia in the cochlear nucleus and in the superior olivary complex ( Foran et al, 2017 ). The physiological effects of glutamate excitotoxicity therefore are concluded to include ARHL ( Pujol et al, 1993 ) and tinnitus ( Brozoski et al, 2012 ; Sahley et al, 2013 ; Yu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that GPIAS can be used in rats 8,15,16 , mice [17][18][19][20] and guinea pigs 11,21,22 . In addition, it has been used after a variety of tinnitus-inducing methods such as after salicylate or quinine 15,23 as well as after acoustic overexposure 16 . Specific parameters, such as the frequency of the background noise and intensity of the startle stimuli used by the different research groups, vary dependent on the natural audiograms of the species used and on the method used to induce tinnitus 15,16,24 .…”
Section: Introductionmentioning
confidence: 99%